Environments and lifting mechanisms of cold-frontal convective cells during the warm season in Germany - G. Pacey; G. Pacey; S. Pfahl; L. Schielicke (Weather and Climate Dynamics, 2025)
Convection often initiates in proximity to cold fronts during the warm season, but how various processes favour convective initiation at different regions relative to the front is still not well-understood. By combining automatic front detection methods and a convective-cell tracking and detection dataset, the environments and availability of different lifting mechanisms are analysed. Our results indicate that pre-surface-frontal cells form in the environments with the highest surface dew points and convective available potential energy (CAPE). Behind the surface front, cells form in environments with lower CAPE and surface dew points, though they are still significantly higher than regions without cells. Mid-level relative humidity discriminates particularly well between post-frontal cell locations and regions without cells. Pre-surface-frontal cells form in environments with the strongest synoptic-scale lifting at 700 hPa and also with the strongest convective inhibition. We also observe the importance of post-frontal synoptic-scale lifting, particularly at 500 hPa. Observational sunshine duration data indicate less sunshine before cell initiation compared to regions without cells in most front-relative regions, which highlights that solar heating may not be responsible for the majority of cold-frontal cell initiation. The results in this study are an important step towards a deeper understanding of the drivers of cold-frontal convection at different regions relative to the front.